Effect of half-marathon running on arterial stiffness and blood biomarkers in high-level and recreational male athletes - Jürgenson, J.; Serg, M.; Kampus, P.; Kals, J.; Zagura, M.; Zilmer, K.; Zilmer, M.; Eha, J.; Unt, E. (Journal of Sports Science & Medicine, 2021)
There is no clear understanding about the effect of intensive physical load on arterial stiffness and related biomarkers. The aim of this study was to evaluate the effect of half-marathon running on arterial stiffness and blood biomarkers during post-competitive recovery period in competitive and recreational male athletes. Eleven high-level long-distance runners (27.1 ± 4.8 yrs) and seven recreational athletes (34.3 ± 6.1 yrs), who participated in a half-marathon run were examined. Blood biomarkers and arterial stiffness (SphygmoCor 7.1) were measured at baseline and at 18 to 22 hours after the competition. There were no statistically significant changes between the groups in augmentation index (AIx, AIx@75) or pulse wave velocities at carotid-femoral segment (cfPWV) during recovery period. Between-group comparison did not reveal significant differences in blood pressure and arterial stiffness values at baseline and during recovery period. The change of cfPWV (difference between cfPWV at baseline and cfPWV during post-competitive recovery period) was significantly dependent on race time and sports level of the athlete (high-level or recreational). A significant increase was found in hsCRP, creatine kinase and LDH activity during the post-race period in both groups. No significant changes were found in oxidative stress markers in the groups after the race except for higher diene conjugates level in recreational athletes in comparison with the high-level group during recovery period. Our study results showed that half-marathon competition did not cause any significant changes in arterial stiffness parameters during the recovery period. However, the change in cfPWV was independently associated with half-marathon race time and the athlete`s level of training revealing a mild increase of arterial stiffness in high-level athletes and athletes with a faster race time.